Genesis of BIF-hosted hematite iron ore deposits in the central part of the Maremane anticline, Northern Cape Province, South Africa - Land, Jarred (Rhodes University, Faculty of Science, Department of Geology, 2014)
The Paleoproterozoic Transvaal Supergroup in the Northern Cape Province of South Africa is host to high-grade BIF-hosted hematite iron-ore deposits and is the country's most important source of iron to date. Previous work has failed to provide a robust and all-inclusive genetic model for such deposits in the Transvaal Supergroup; in particular, the role of hydrothermal processes in ore-genesis has not been adequately clarified. Recent studies by the author have produced evidence for hydrothermal alteration in shales (Olifantshoek Supergroup) stratigraphically overlying the iron-ore intervals; this has highlighted the need to reassess current ore-forming models which place residual supergene processes at the core of oregenesis. This thesis focuses on providing new insights into the processes responsible for the genesis of hematite iron ores in the Maremane anticline through the use of newly available exploration drill-core material from the centre of the anticline. The study involved standard mineralogical investigations using transmitted/reflected light microscopy as well as instrumental techniques (XRD, EPMA); and the employment of traditional whole-rock geochemical analysis on samples collected from two boreholes drilled in the centre of the Maremane anticline, Northern Cape Province. Rare earth element analysis (via ICP-MS) and oxygen isotope data from hematite separates complement the whole-rock data. Iron-ore mineralisation examined in this thesis is typified by the dominance of Fe-oxide (as hematite), which reaches whole-rock abundances of up to 98 wt. % Fe₂O₃. Textural and whole-rock geochemical variations in the ores likely reflect a variable protolith, from BIF to Fe-bearing shale. A standard supergene model invoking immobility and residual enrichment of iron is called into question on the basis of the relative degrees of enrichment recorded in the ores with respect to other, traditionally immobile elements during chemical weathering, such as Al₂O₃ and TiO₂. Furthermore, the apparently conservative behaviour of REE in the Fe ore (i.e. low-grade and high-grade iron ore) further emphasises the variable protolith theory. Hydrothermally-induced ferruginisation is suggested to post-date the deposition of the post-Transvaal Olifantshoek shales, and is likely to be linked to a sub-surface transgressive hydrothermal event which indiscriminately transforms both shale and BIF into Fe-ore. A revised, hydrothermal model for the formation of BIF-hosted high-grade hematite iron ore deposits in the central part of the Maremane anticline is proposed, and some ideas of the author for further follow-up research are presented.
Keywords: Hematite -- South Africa -- Northern Cape; Anticlines -- South Africa -- Northern Cape; Geology, Stratigraphic -- Proterozoic; Hydrothermal deposits -- Northern Cape; Rare earth metals -- Northern Cape; Iron ores -- Geology -- Northern Cape; Transvaal Supergroup (South Africa)